LATIHAN INTERVAL EKSTENSIF UNTUK DAYA TAHAN DAN KECEPATAN LARI 400 METER ATLET PPLP NTB - Mahdalena Sari; Herman Syah; Ali Imran (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
ABSTRACT Endurance and speed are important components in the 400-meter sprint event because athletes are required to maintain sprint performance until the finish line. One of the common problems experienced by sprint athletes is a decrease in speed during the final phase of the race due to high levels of fatigue. This study aimed to analyze the effect of extensive interval training on improving the endurance and speed abilities of 400-meter runners at PPLP NTB athletics. The study employed an experimental method using a one group pretest-posttest design. The research sample consisted of 10 PPLP NTB athletics athletes selected through a total sampling technique. The training program was conducted for six weeks with a frequency of three sessions per week and a total of 16 meetings. The training program consisted of 500-meter runs with a target time of 80 seconds, two sets, two-minute recovery, and a gradual increase in repetitions from three to seven repetitions. The research instrument used was a 400-meter running test measured in seconds. Data were analyzed using descriptive statistics and a paired sample t-test at a 5% significance level. The results showed that the average 400-meter running time decreased from 61.92 seconds in the pretest to 55.68 seconds in the posttest. Statistical analysis revealed that the t-count value of 6.333 was higher than the t-table value of 1.833. These findings indicate that extensive interval training is effective in improving the endurance and speed performance of 400-meter athletes. ABSTRAK Penelitian ini dilatarbelakangi oleh pentingnya kemampuan daya tahan dan kecepatan dalam lari 400 meter, karena nomor ini menuntut kemampuan mempertahankan kecepatan tinggi sampai garis akhir. Penelitian bertujuan untuk mengetahui pengaruh latihan interval ekstensif terhadap peningkatan kemampuan daya tahan dan kecepatan lari 400 meter atlet atletik PPLP NTB. Penelitian menggunakan metode eksperimen dengan desain two group pre-test and post-test. Sampel penelitian berjumlah 10 atlet atletik PPLP NTB yang diambil dari seluruh populasi penelitian. Instrumen penelitian berupa tes lari 400 meter dengan satuan detik, menggunakan lintasan atletik, start block, stopwatch, cone, dan blangko pencatatan. Perlakuan diberikan selama enam minggu dengan frekuensi tiga kali setiap minggu dan total 16 kali pertemuan. Program latihan menggunakan lari 500 meter dengan target waktu 80 detik, dua set, repetisi bertahap dari tiga sampai tujuh kali, dan recovery dua menit. Data dianalisis menggunakan statistik deskriptif dan uji t. Hasil penelitian menunjukkan bahwa rata-rata waktu kelompok interval menurun dari 61,92 detik pada pretest menjadi 55,68 detik pada posttest. Hasil uji t menunjukkan nilai t-hitung sebesar 6,333 lebih besar daripada t-tabel 1,833 pada taraf signifikansi 5%. Dengan demikian, latihan interval ekstensif berpengaruh terhadap peningkatan kemampuan daya tahan dan kecepatan lari 400 meter atlet atletik PPLP NTB.